STAKEHOLDERS’ EXPERIENCES ON THE ESTABLISHMENT AND SUSTAINABILITY OF THE BALAY PAGLAUM - Batulan-Añonuevo, Ailene; Santos, Edgardo M (PEOPLE: International Journal of Social Sciences, 2019)
This phenomenological study explored the underlying framework on the establishment and sustainability of the Balay Paglaum (House of Hope) through the lived experiences of the stakeholders which served as informants and were selected based on their first-hand ideas on the challenges encountered and strategies employed to overcome difficulties and the binding realizations they gained throughout the process of establishing and sustaining the Balay Paglaum. Stakeholders used were from the Local Government Unit, Department of Education and Indigenous Peoples’ group. Based on their shared experiences 6 themes emerged and 21 clustered themes surfaced. With its establishment, the dropout rate problem of the Indigenous Peoples (IPs) was addressed and resolved. Commitment, love for the IP learners, enthusiasm of the leaders, believing the worth of the project and strong partnership made the Balay Paglaum become sustained and recognized as a shelter where hopes and dreams of the IPs are realized. It also served as the scaffold of the IP learners while pursuing their Basic Education.